2022
DOI: 10.1088/1361-6463/ac918e
|View full text |Cite
|
Sign up to set email alerts
|

A bipolar charge transport model to simulate the impact of nanometric scale processes on the space charge behaviour in polyethylene

Abstract: Predicting the electric field distribution in polymers used as electrical insulating materials remains the Holy grail, as the presence of charges disturbs the Laplacian electric field. Charges arising from the electrodes are one of the dominant mechanism of charge generation, particularly in polyethylene-based materials. Hence, nanometric scale processes at play at the interface have a non negligible impact on charge injection. In the present study, a bipolar charge transport model developed in 2D is used to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A modified bipolar charge injection and transport model based on the Schottky injection mechanism is established to investigate the charging behavior in polymer/organic molecular semiconductors all-organic polymer composites under high operating voltage [12,20]. The current density at the interface between the electrode and the polymer/organic molecular semiconductors all-organic polymer is presented as [9,12,21],…”
Section: Methodsmentioning
confidence: 99%
“…A modified bipolar charge injection and transport model based on the Schottky injection mechanism is established to investigate the charging behavior in polymer/organic molecular semiconductors all-organic polymer composites under high operating voltage [12,20]. The current density at the interface between the electrode and the polymer/organic molecular semiconductors all-organic polymer is presented as [9,12,21],…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, combining with the general solution of Equation ( 6) in plural form, the solution of voltage wave in Equation ( 5) characterizing the transmission line model is shown in Equation (8). u(x, t ) = U (x)e j 𝜔t = A 1 e −𝛼 0 x e j (𝜔t −𝛽 0 x) + A 2 e 𝛼 0 x e j (𝜔t +𝛽 0 x) (…”
Section: Equivalence Of Acoustic Wave and Voltage Wave Propagationmentioning
confidence: 99%
“…From the basic equations of acoustic wave propagation in Equation (1) and voltage wave propagation in Equation (6) with their corresponding solutions in Equations ( 3) and (8), it can be found that the characterizations of the two waves are similar. It means that these two wave propagation processes can be equivalent to each other.…”
Section: Equivalence Of Acoustic Wave and Voltage Wave Propagationmentioning
confidence: 99%
See 1 more Smart Citation